Green Inside Activism for Sustainable Development Political Agency and Institutional Change - Hysing, Erik (Springer International Publishing, 2018)
This book considers how public sector institutions can be transformed to better support sustainable development by exploring the concept of green inside activism and its importance for institutional change. The phenomenon of inside activism has been shown to be crucial for green policy change and this book focuses on public officials as green inside activists, committed to green values and engaged in social movement, acting strategically from inside public administration to change public policy and institutions in line with such value commitment. The book theorizes how green inside activism can contribute to a more sustainable development through institutional change. This theorizing builds on and relates to highly relevant theoretical arguments in the existing literature. The authors also consider the legitimacy of inside activism and how it can be reconciled with democratic ideals. This innovative work will appeal to students and scholars of public policy, political science and environmental politics.